Design and Verification of Near Space Target Interceptor Trajectory - Chen Wenyu, Shao Lei, Tan Shili, Xu Chenyang, Li Shijie (Editorial Office of Aero Weaponry, 2021)
The trajectory of the near space hypersonic target interceptor is designed and verified. Firstly, this paper discusses the necessity of the trajectory design of the near space hypersonic target interceptor. Taking the high throw-reentry-glide trajectory scheme of the near space hypersonic as the reference trajectory, the whole trajectory is divided into active phase and glide phase. Secondly, the active phase takes the longest range as the performance index, and the glide phase takes the maximum terminal velocity as the performance index. According to the constraints of flight process analysis, it establishes the optimal control model of trajectory optimization. Lastly, the Gauss pseudo-spectral method is used to plan the trajectory of the active and gliding phases. The simulation results show that the obtained trajectory characteristics are consistent with the high-throw-reentry-glide trajectory scheme, and the flight parameters satisfy the constraints. This study can provide some reference for the trajectory planning of the near-space interceptor.